Photocatalytic studies of TiO2 nanomaterials prepared via facile wet chemical route. (2017) - Harlapur, Sujatha F.; Rashmi, B.N.; Nagaswarupa, H.P.; Prashantha, S.C.; Shashishekar, T.R.; Anil Kumar, M.R.
Abstract: TiO2 nanomaterials (NPs) were synthesized by a green mediated combustion route by using Aloe Vera peel. The obtained products were characterized by PXRD, DRS and SEM. PXRD patterns show typical anatase phase with peaks at 2θ = 25.3, 37.7, 47.8, 54, and 62.7 and rutile phase with peaks at (2θ = 26.5 and 40.0) which is in agreement with 21-1272 standard card from JCPDS. The crystallite size calculated from Scherrer's formula was found to be in the range 20-45 nm. SEM images clearly reveal that irregular, pourous and cone type morphologies. The optical band gap decreases from 3.50eV to 3.20eV and it is confirmed by DRS. Further, it was investigated for the PC decolorization of Malachite green. The enhanced photocatalytic activity of TiO2 was attributed to effective crystallite size, textural properties, decreased band gap and capability for reducing the electron–hole pair recombination. These findings open up new avenues for the exploration of TiO2 in eco-friendly water applications.